Journalist's Strategy Tras.Id in Search of News in Bengkulu Province - Uthami, Apnita Noor; Yuliati, Yuliati; Mujni, Nurlianti (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
Every day journalists are required to be able to find and make news. With these demands, journalists are encouraged to be able to fulfill them in various ways in accordance with the rules and regulations. This paper shows the strategies of Tras.id journalists in finding news in the Bengkulu Region. Purposive sampling, an informant interview technique, was used in this qualitative research. Planning, production, and editing are the three main focuses of this research. This study uses data collection methods with observation, interviews, and documentation to collect information from six people, namely the public, editor-in-chief, editors, and journalists. Starting with daily editorial meetings and the availability of supporting equipment such as cars, cell phones, agendas/notebooks, and press cards, this research resulted in a news search strategy. The study's recommendations focus on two areas: the lack of case studies or specific topics on the news published by Tras.id media and the need to initiate some major investigations into the escalation of political issues. The next advice that needs to be given is to pay close attention to each sentence on the news page before it is published.